The Modulatory Effect of Iraqi Propolis Extract on Mitomycin-C Induced Microneulcus Formation in Albino Male Mice - Al-Halbosiy, Mohammed M. F. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Propolis (bee glue) is a resinous hive product. It consists of exudate from plants mixed with beeswax and used be bees as glue in general-purpose as sealer and draught-exclude for beehives. Propolis, used in folk medicine, has attracted researchers attention to elucidate its therapeutic properties, as antioxidant and anticancer. Therefore, the study aimed to investigate the role of propolis in modulating effects of mitomycin C; MMC. Methods: Ethanolic solutions of propolis were prepared and administered to albino male mice (Mus musculus) through three types of experiments. In the first, the propolis was tested alone, while in the second and third experiments, propolis was given orally before and after MMC (pre- and post-treatments, respectively). All experiments were paralleled by negative and positive controls. The investigated parameters were total count of leucocytes, mitotic index, micronucleus formation and chromosomal aberrations. Results: In the first experiment, the results indicated that 10 mg/kg/day of propolis enhanced the parameters investigated, and a significant increase was observed in the total count of leucocytes and mitotic index. Also, there was no significant difference in the rate of micronucleus formation and chromosomal aberrations as compared to negative controls. In the second (pre-treatment) and third (post-treatment) experiments, a similar picture was drawn. However, the dose 10 mg/kg/day was more effective in this respect. Conclusion: The results indicate that propolis may act upon the immunological system and has the potential to inhibit the genotoxic effects of MMC. A further study will be needed to determine the effects of compounds isolated from propolis and evaluate the synergistic effects on MI and MN.